Trends in ectopic pregnancy: a retrospective clinical study of 79 cases - M., Sindhura; R., Sailatha; M., Famida A.; K., Vijayalakshmi; S., Sathiya; S., Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To know the age group, parity, risk factors, clinical features, modalities of treatment employed and their efficacies, morbidity and mortality associated with ectopic pregnancy. Methods: This is a retrospective study conducted in the department of Obstetrics and Gynaecology at Chettinad Hospital and Research Institute; Chennai over a period of 3 years from January 2014 to December 2016. A total number of 79 cases of ectopic pregnancies were reported during this period. Data were collected, tabulated and analyzed. Results: 79 cases were diagnosed as ectopic pregnancies during the study period giving an incidence of 3.49%. Incidence of cases was maximum in women between the age group of 26-30 years (40.50%), in multiparous women (72.15%) and also in women of gestational age between 6 to 10 weeks (81.01%).72% of the cases had one or more identifiable risk factors. Ruptured ectopic was observed in 45 (56.96%)cases while unruptured in 31 (39.24%) cases. Tubal abortion was found in 3 (3.74%) cases. 2.53% cases were expectantly managed. 34.17% cases were medically managed. 63.29% cases were managed surgically. Morbidity due to ectopic pregnancy included anaemia, wound infection, SICU admission. No mortality observed. Conclusions: A high index of suspicion is needed in the diagnosis of ectopic pregnancy especially in women with high risk factors to arrive at early diagnosis, followed with conservative management, thus reducing the morbidity. We can reduce the incidence of ectopic pregnancy by awareness on safe sexual practices and contraception. The lady’s future fertility can be improved by focusing on prevention, early diagnosis and conservative management of ectopic pregnancy.